Serum Neuron-specific Enolase Levels in Preterm and Term Newborns and in Infants 1-3 Months of Age - Aslihan Abbasoglu; Faik Sarialioglu; Nalan Yazici; Nilufer Bayraktar; Aysegul Haberal; Ayse Erbay (Elsevier, 2015)
Elevated serum levels of neuron-specific enolase (NSE) was initially assumed to be specific to neuronal tumors (particularly neuroblastoma), but is now known to accompany nontumoral conditions and tumors other than neuroblastomas. There is a need to establish normal ranges for NSE, especially in early infancy. The aims of this study were to determine reference values for NSE in newborns and young infants and to assess whether NSE levels in early infancy (i.e., preterm infants and term infants) differ from the adult reference range for this enzyme. Methods: We enrolled 140 healthy babies, which included 40 preterm newborns (3-15 days old and born at 28-42 weeks gestation), 40 term newborns (< 1 month old and born at term), and 60 young infants 1-3 months old (n = 20 per subgroup of 1-, 2-, and 3-month-old infants). The determination of NSE levels was performed by the electrochemiluminescence immunoassay (ECLIA) method using the Elecysys 2010 device (Roche Diagnostics, Mannheim, Germany). The mean serum NSE levels for the preterm newborns was 21.83 ± 15.06 ng/mL [95% confidence interval (95%CI), 16.95-26.71 ng/mL]; term newborns, 18.06 ± 12.83 ng/mL (95%CI, 13.94-22.19 ng/mL); and young infants, 9.09 ± 4.38 ng/mL (95%CI, 7.96-10.23 ng/mL). The mean serum NSE level for infants 1-3 months old was within the ECLIA kit's normal range (4.7-18 ng/mL for adults), whereas the corresponding means for the preterm and term newborns were higher (p < 0.001, for both). Conclusion: Our findings suggest that adult reference values should not be applied to the preterm and term age groups.